2018
DOI: 10.1111/1365-2664.13131
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of game bird management for non‐game species in Europe

Abstract: Game bird management has the potential to benefit conservation, as management practices specifically targeted at reducing the factors limiting game populations may have positive effects on non‐game species. However, such management may also have costs to species. We review the literature that examines the effect of different forms of game bird management on non‐target species in Europe, including habitat management, predator control, parasite control, provision of water and food and rear and release. We focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 97 publications
(188 reference statements)
0
26
0
Order By: Relevance
“…Likewise, studies of supplementary feeding in the UK have been relatively small and localised, and we suggest a review of their efficacy and their extension to consider their effects in different conditions and locations. Such landscapescale interventions (predator control and supplementary feeding) likely have unintended positive consequences for wildlife beyond game (Mustin et al 2018;Roos et al 2018). We suspect that both methods do improve the survival of released birds and effects are currently concealed because all game managers practise them over much of the UK with little opportunity for representative control sites to be assayed, but further, directed studies are required to confirm this.…”
Section: Changing Management Actionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, studies of supplementary feeding in the UK have been relatively small and localised, and we suggest a review of their efficacy and their extension to consider their effects in different conditions and locations. Such landscapescale interventions (predator control and supplementary feeding) likely have unintended positive consequences for wildlife beyond game (Mustin et al 2018;Roos et al 2018). We suspect that both methods do improve the survival of released birds and effects are currently concealed because all game managers practise them over much of the UK with little opportunity for representative control sites to be assayed, but further, directed studies are required to confirm this.…”
Section: Changing Management Actionsmentioning
confidence: 99%
“…Regardless, there is a general pattern of increased release numbers over the past 50 years, with around nine times as many pheasants released in 2011 compared to 1961 when monitoring began (Robertson et al 2017). Consequently, they now comprise around 23% of the mass of the UK bird breeding population (Eaton et al 2012) and hence constitute a potentially influential component of the British ecosystem (Mustin et al 2018, Roos et al 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shooting of game birds has a long history and is widespread across North America, Europe, and beyond (Mustin et al, ; Mustin, Newey, Irvine, Arroyo, & Redpath, ; Rashkow, ). Orders of magnitude more pheasants than lions are killed annually by sport hunters.…”
Section: Pheasant Shootingmentioning
confidence: 99%
“…These habitats have benefits for the conservation of wildlife including pollinators (Holland, Smith, Storkey, Lutman, & Aebischer, ), passerines (Draycott et al, ; Stoate, ), small mammals (Tew, Macdonald, & Rands, ) and hares (Meichtry‐Stier, Jenny, Zellweger‐Fischer, & Birrer, ; Petrovan, Ward, & Wheeler, ). In their literature review of the effect of different forms of game bird management on non‐target species in Europe, Mustin et al () found that 85% of the effects of habitat management for game birds in lowland agricultural landscapes were positive. However, there were few studies of the effects on non‐game species of rear‐and‐release and supplementary feeding of game birds.…”
Section: Pheasant Shootingmentioning
confidence: 99%